# Solve this problem by using elimination: 2x-3y=61 and 2x+y=-7

Saturday, July 24th, 2010

### Solution:

- 2x – =y=61
- 2x + y= -7

If you subtract the second equation from the first, you can eliminate x and you are left with **-4y = 68.**

So **y =3D -17**, and plugging this into the first equation we can figure out

y: 2x = (-51)=61,

so **x = 5**

Tags: 9th Grade, Homework Answers, Math, Math Answers

Posted in

Posted in

**9th Grade, Homework Answers, Math Answers**.This entry was posted on **Saturday, July 24th, 2010** at **2:41 am** and is filed under **9th Grade, Homework Answers, Math Answers**. You can follow any responses to this entry through the **RSS 2.0** feed.
You can **leave a response**, or **trackback** from your own site.